Understanding the hidden meaning of Death of a Salesman (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
This paper focuses on analyzing the drama script entitled Death of a Salesman as one of the representations of literary work in the modern period using the deconstructive approach. The purpose of this study is to figure out the hidden meaning about the American Dreams represented by Willy Loman. The method used in this paper is descriptive qualitative. This paper uses deconstructive approach from Jacques Derrida. The result of this research shows the belief of the American Dreams cannot be applied in the modern era to all of Americans. Most Americans hold a strong belief that everyone will get a happiness and a successful life in America. This deconstructive analysis finds a hidden meaning that the belief of the American Dreams could not guarantee the success of people who live in America. Death of a Salesman represents the character of Willy Loman as an American who fail to accomplish his success to be a salesman, a husband, and a father.